2010
DOI: 10.2223/jped.2033
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors contributing to childhood poisoning

Abstract: Objective: To investigate whether the lack of knowledge of toxic agents in households is a risk factor for individual unintentional childhood poisoning. Methods:The case group (n = 25) was composed of caregivers of children under 60 months of age who underwent accidental oral poisoning and were treated at two reference hospitals in Porto Alegre, southern Brazil, and recorded in the Toxicology Information Center database. The control group (n = 25) was composed of caregivers of children matched for sex, age, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 25 publications
(28 reference statements)
3
22
1
4
Order By: Relevance
“…Drugs should be stored out of reach of children. In fact, a sudy in Brasil showed that storage of drugs lower than 150cm increase the chances of drug poisoning in children 28 and we recommend that a law should be introduced to caution parents on ways of storing drugs. The establishment of Poison Control and Information Centres in each of the six geopolitical regions of Nigeria and a National Centre in Abuja should be introduced and given an easy telephone which can be memorised.…”
Section: Resultsmentioning
confidence: 96%
“…Drugs should be stored out of reach of children. In fact, a sudy in Brasil showed that storage of drugs lower than 150cm increase the chances of drug poisoning in children 28 and we recommend that a law should be introduced to caution parents on ways of storing drugs. The establishment of Poison Control and Information Centres in each of the six geopolitical regions of Nigeria and a National Centre in Abuja should be introduced and given an easy telephone which can be memorised.…”
Section: Resultsmentioning
confidence: 96%
“…An Australian study of children aged 1–3 years attending an ED following a poisoning and hospital and community controls found accessible storage of medicines in bathrooms increased the odds of poisoning (OR 1.03, 95% CI 1.002 to 1.080) 7. Two studies using children aged 0–4 years treated in hospital for poisoning and hospital controls found storing toxic substances in boxes/cabinets (OR 3.80, 95% CI 1.15 to 12.49) or <150 cm from the floor (OR 16.59, 95% CI 2.86 to 96.20)8, unsafe storage of chemicals and medicines (OR 5.6 95% CI 1.9 to 16.7) and storing kerosene and petrol in soft drink bottles (OR 3.8, 95% CI 2.0 to 7.3) increased the odds of poisoning 9. In contrast, two small studies failed to find significant associations between safely packaged household products,10 presence of toxic substances, storage practices, frequencies of use, packaging or disposal and poisonings 11.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports of lead-related fatalities from Senegal (Haefliger et al 2009), where the World Health Organization (WHO) confirmed at least 18 children died from lead poisoning. Additionally, there are many reports of extremely elevated blood lead levels from other countries (Nduka et al 2008;Orisakwe and Nduka 2009;Shi et al 2009;Brown et al 2010;Niu 2010;Norman et al 2010;Ramos et al 2010;Rowley 2010). In most of these reports, the average BLLs reported were > 65 μg/dL, levels considered to be life-threatening to children (CDC 2002).…”
Section: Introductionmentioning
confidence: 99%